Os museus de Pedrosa: uma contra narrativa para a arte brasileira - Ana Cecília Araújo Soares de Souza (2023)
This research aims to discuss the museological projects elaborated by Mário Pedrosa (1900-1981) from the analysis of the Museum of Brasília, designed, in 1958, at the invitation of Oscar Niemeyer (1907-2012), for the new Federal Capital; the Museum of Solidarity, of which the Brazilian critic was one of the main articulators, between 1971 and 1973, in Santiago, Chile; and the Museum of Origins (MO), which emerged as a solution to the fire suffered by the Museum of Modern Art of Rio de Janeiro (MAM-RJ), in 1978, whose purpose was to create and take advantage of existing museums, categorizing them as representatives of following types of production: virgin art by children and psychiatric patients from the Engenho de Dentro studio; indigenous art, black art; modern art and popular art. Although Pedrosa did not see any of these proposals actually realized (the Museu da Solidariedade was the closest to a realization), the immersion in these three museums allowed us to investigate nuances and lucubrations of his museological look, resulting from a series of experiences his in the field of art and politics, especially in relation to the last exile he experienced in Chile, in the 1970s. As a hypothesis, we believe that Pedrosa's museum projects paved the way for the conflagration of a counter-narrative, of a genealogy, where the MO would be the apex, the high point of maturation of an entire thought that seeks to break with the vanguard idea and with the hegemonic thought of Europe and the United States. As for the development of this study, we used the historiographic methodology constituted by the bibliographic systematization and the analysis of the existing primary sources in the documentary collections of the Salvador Allende Solidarity Museum and the Museum of Contemporary Art of Santiago in Chile. Finally, among the authors who helped us in the construction of this thought, we highlight the studies of Edward Said (1935-2003); Benedict Anderson (1936-2015); Frantz Fanon (1925-1961); Cristiana Tejo, Ana María Risco, Izabela Pucu, Luíza Mader, Pollyana Quintella and Mário Chagas.